Proses Morfologis Penggabungan Gairaigo Dalam Majalah Lips Volume 29 - Rilenca, Cendy (Humanis; Volume 17. No. 1. Oktober 2016)
The aims of this study is to find out morphological of compound words of gairaigo in Lips Magazine volume 29. This study especially discusses about morphological of  compound words of gairaigo and the meaning of compound words of gairaigo in Lips Magazine volume 29. The data were analyzed using qualitative analysis method. First, the data collection was done with the methods “simak”. The one that was already collected analyzed by a method of “descriptive”. Then the results of the analysis served by using the method “informal”. This study used the theory from O’Grady, Dobrovolsky, and Katamba (1996) and Chaer (2009). The conclusion of this study is the morphological of compound words of gairaigo can be devided into three categories . They are nominal compound of gairaigo, verbal compound of gairaigo, and adjectival compound of gairaigo. Meanwhile, base on its meaning to origin words, the compound words of gairaigo can be devided into three categories, which are: the meaning of compound word of gairaigo which suitable to its two origin words, the meaning of compound word of gairaigo which derived from one of its origin word, the meaning of compound word of gairaigo which are not suitable to its two origin words.
Keywords: morphology, compounding, gairaigo